Characterisation of T cell clonotypes that accumulated in multiple joints of patients with rheumatoid arthritis. Issue 9 (1st September 1999) - Kurokawa, Manae; Kato, Tomohiro; Masuko-Hongo, Kayo; Ueda, Shin-ichiro; Kobata, Tetsuji; Okubo, Mitsuo; Nishimaki, Tomoe; Akaza, Tatsuya; Yoshino, Shin-ich; Kasukawa, Reiji; Nishioka, Kusuki; Yamamoto, Kazuhiko
Abstract : OBJECTIVE: To investigate whether identical T cell clonotypes accumulate in multiple rheumatoid joints, the clonality of T cells that had infiltrated into synovial tissue (ST) samples simultaneously obtained from multiple joints of patients with rheumatoid arthritis (RA) was analysed. METHODS: T cell receptor (TCR) β gene transcripts, amplified by reverse transcription-polymerase chain reaction from ST and peripheral blood lymphocytes of five RA patients, were subjected to single strand conformation polymorphism analysis and DNA sequencing. RESULTS: Approximately 40% of accumulated T cell clonotypes found in one joint of a patient were found in multiple joints in the same patient. Furthermore, identical amino acid sequences were found in TCR β junctional regions of these clonotypes from different patients with at least one HLA molecule match. CONCLUSIONS: The T cell clonotypes accumulating in multiple rheumatoid joints may be involved in the perpetuation of polyarthritis by reacting to antigens common to these multiple joints.